Q: What is 4t equals 24?

Write your answer...

Submit

Related questions

9t = 4t + 120 9t-4t = 4t - 4t + 120 5t = 120 5t/5 = 120/5 t = 24 24 is your answer

4t - 6 = 4*(-6) -6 = -24 -6 = -30

10t=6t+24 -6 -6 4t=24 4 4 1=6 t=6

If 4t + 5 = 37, then t = 8.

4t - 3 = 19 4t = 19 +3 = 22 t = 22/4 t = 5.5

4T

-2t = -10

8,000 lbs

t in this problem equals -3. 4t- 8+ 25= 5 -25 -25 4t- 8= -20 +8 +8 4t= -12 /4 /4 t= -3

8625lb

2

math

T+(3-2t)=4t+1. Assuming the two T's , T and t are the same variable, lets proceed. t+(3-2t)=4t+1 3-t=4t+1 2-t=4t 2=5t last step is yours

It is an equation and the value of t is 1

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1

Subtract 21 from both sides. If that's + 4t, the answer is (t - 3)(t + 7) and t = 3, -7 If that's - 4t, the answer is (t + 3)(t - 7) and t = -3, 7

t + 10 - 4t = -11 Subtract 10 from each side: t - 4t = -21 ie -3t = -21 t = -21/-3 t = 7.

It should, since 4T equals a quarter cup.

NEVERMIND!

r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)

You don't have enough information to solve this. You need to know what P is, or what T is, otherwise you can't get an answer.

4t-7=3y-4 y=3

100 cft = 1 unit 4ton = 1 unit

In the expression 5-4t it is t that is the variable